Africa, Latin America, and the Caribbean : the case for bilateral and multilateral cooperation - Abidde, Sabella Ogbobode, 1962- (Lexington Books, 2018)
"Despite their shared history and the potential benefits of cooperation in the twenty-first century, a bilateral and multilateral relationship among Africa, Latin America, and the Caribbean remains an overlooked possibility. Using a multidisciplinary approach, this book advocates for increased and renewed cooperation among the regions"--